Application of Pyramidal Decomposition to Improve Digital Radiography Image Quality - Setiawan, Rudi; Susilo, Susilo (Universitas Negeri Semarang, 2023)
As an effort to create innovation in the world of radiography, it is necessary to develop technology in software. This effort is to improve image quality by using pyramidal decomposition. This digital image decomposition is referred to as pyramid decomposition. The original image is decomposed into several frequency bands, repeatedly divided into high-pass components and low-pass components. The high-pass component is set aside while the low-pass image is subjected to subsequent division. This creates a kind of